2019
DOI: 10.1111/plb.13060
|View full text |Cite
|
Sign up to set email alerts
|

Heteromorphic seeds of wheat wild relatives show germination niche differentiation

Abstract: Crop wild relatives are fundamental genetic resources for crop improvement. Wheat wild relatives often produce heteromorphic seeds that differ in morphological and physiological traits. Several Aegilops and Triticum species possess, within the same spikelet, a dimorphic seed pair, with one seed being larger than the other. A comprehensive analysis is needed to understand which traits are involved in seed dimorphism and if these aspects of variation in dimorphic pairs are functionally related. To this end, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…aegilopoides showed variable behaviours in terms of heteromorphism when subjected to the two storage environments (AA, SB). In previous studies we demonstrated that different morphs of the same species respond differently to AA in several wheat wild relatives, with smaller seeds possessing higher longevity, dormancy and antioxidant profiles (Guzzon et al 2018;Gianella et al 2020). These seed traits are known as part of a bethedging evolutionary strategy that allow smaller seeds a longer persistence in the soil (Arshad et al 2019), thereby spreading the risk of germination failure over time.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…aegilopoides showed variable behaviours in terms of heteromorphism when subjected to the two storage environments (AA, SB). In previous studies we demonstrated that different morphs of the same species respond differently to AA in several wheat wild relatives, with smaller seeds possessing higher longevity, dormancy and antioxidant profiles (Guzzon et al 2018;Gianella et al 2020). These seed traits are known as part of a bethedging evolutionary strategy that allow smaller seeds a longer persistence in the soil (Arshad et al 2019), thereby spreading the risk of germination failure over time.…”
Section: Discussionmentioning
confidence: 96%
“…Probit analysis was carried out using Genstat 9 to obtain the time for viability to fall by 50% (P 50 ), used then as measure for seed longevity by fitting the viability equation (Ellis & Roberts, 1980) as previously described by Gianella et al . (2020). P 50 s, estimated in triplicate, were compared between seed lots belonging to the same species and subjected to the same ageing conditions (AA or SB) using Student t‐ tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, when subjected to accelerated ageing, heteromorphic caryopses of Aegilops and of Triticum urartu Thum. ex Gandilyan (Poaceae) showed different lifespans and antioxidant activities: the shorter-lived, larger morphs possess lower antioxidant activities when compared to their smaller, darker and longer-lived counterparts (Gianella et al 2020).…”
Section: Impact On Seed Physiologymentioning
confidence: 99%
“…From an ecological point of view, most of the studies on bet-hedging have focused on just one phenotypic trait, such as seed longevity (Guzzon et al 2018) or resistance to abiotic stresses during germination (Bhatt and Santo 2016). Further studies are needed to consider simultaneously the different traits influenced by bet-hedging in order to clarify the ecological trade-offs involved in this strategy in different plant species (Gianella et al 2020). Moreover, a more comprehensive phylogenetic analysis is needed to assess the presence of bet-hedging and its evolutionary significance in the whole phylum, considering taxa from all over the globe (Scholl et al 2020;Gioria et al 2020).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%